Peran Partisipasi Anggaran, Kejelasan Sasaran Anggaran, dan Komitmen Sebagai Pemediasi Terhadap Kinerja Aparatur Pemerintah - Irmayanti Sudirman (Al-Buhuts, 2024)
This research aims to examine the influence of budget participation, clarity of budget targets, commitment as a mediator on the performance of government officials. This research method uses primary data, namely the results of questionnaires from all respondents with a sample size of 145 respondents from 57 SKPD in South Sulawesi. This research used a Structural Equation Modeling analysis tool based on Partial Least Square or SEM PLS version 23. The results of this research show that budget participation influences the performance of government officials. Clarity of budget targets influences the performance of government officials. Commitment is able to mediate budget participation on the performance of government officials. Furthermore, commitment is able to mediate clarity of budget targets on the performance of government officials.